2008
DOI: 10.1073/pnas.0806074105
|View full text |Cite
|
Sign up to set email alerts
|

Age-related top-down suppression deficit in the early stages of cortical visual memory processing

Abstract: In this study, electroencephalography (EEG) was used to examine the relationship between two leading hypotheses of cognitive aging, the inhibitory deficit and the processing speed hypothesis. We show that older adults exhibit a selective deficit in suppressing task-irrelevant information during visual working memory encoding, but only in the early stages of visual processing. Thus, the employment of suppressive mechanisms are not abolished with aging but rather delayed in time, revealing a decline in processin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

67
459
9
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 407 publications
(545 citation statements)
references
References 26 publications
67
459
9
3
Order By: Relevance
“…From this perspective, our neural findings of persistent connectivity for the interruptor may reflect inadequate deletion of information that is no longer relevant. Therefore, this disengagement deficit seems to represent yet another example of failed inhibition in older adults, which has been extensively characterized as a deficit in suppressing distracting information (5,13,15). Thus, this finding serves as a conceptual bridge to unite age-related distraction and interruption effects under a common mechanism.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…From this perspective, our neural findings of persistent connectivity for the interruptor may reflect inadequate deletion of information that is no longer relevant. Therefore, this disengagement deficit seems to represent yet another example of failed inhibition in older adults, which has been extensively characterized as a deficit in suppressing distracting information (5,13,15). Thus, this finding serves as a conceptual bridge to unite age-related distraction and interruption effects under a common mechanism.…”
Section: Discussionmentioning
confidence: 87%
“…Functional MRI measures revealed that older individuals inappropriately direct excessive attention toward processing visual stimuli that are entirely irrelevant (i.e., distractions), and that this correlates with diminished WM performance (13). EEG studies further showed that this occurs early during visual processing (<200 ms after stimulus onset), whether or not individuals are prepared for the distractor (5,(13)(14)(15). Moreover, the degree that both distractors and interruptors are processed correlates with reduced WM performance in both younger and older adults (4,5).…”
mentioning
confidence: 99%
“…Within the first 200 ms, the young adults exhibited the largest P1 amplitude and earliest N1 latency for the attended faces, followed by passive faces and then ignored faces, whereas the older adults only exhibited the largest P1 amplitude and earliest N1 latency for the attended faces compared with passive faces. Gazzaley et al (2008) interpreted these results as an indication of sensory suppression deficits in older adults (because there were no differences between the passive and ignore conditions), as well as an indication of preserved enhancement processes (the same change in young and older adults between the passive and attend conditions). In an additional experiment with the selective attention delayed-recognition task, Anguera and Gazzaley (2012) …”
Section: Age-related Inhibition Changes In the First 200 Msmentioning
confidence: 93%
“…While the behavioral aspects of age-related decline in WM are well known , the changes of functional interactions between brain areas related to WM (especially during the maintenance period) across the lifespan are still largely unclear, and have not as yet been investigated by EEG studies. It is still a matter of debate which WM processes (encoding: Gazzaley et al, 2008;Karrasch et al, 2004, or maintenance: Cappell, Gmeindl, & Reuter-Lorenz, 2010) underlie much of the WM deficits observed in the elderly.…”
Section: Introductionmentioning
confidence: 99%